Allograft nephrectomy vs. no nephrectomy for failed renal transplants - McDonald, Michelle (Frontiers in Nephrology, 2023)
The role of allograft nephrectomy (AN) in a failed renal transplant is a topic of debate due to controversial results reported in the literature and fact most of the studies are flawed by the retrospective design and small numbers. Allograft nephrectomy is most likely of benefit in the patient with recurrent allograft intolerance syndrome (AIS) following pulse steroids. Immunosuppression weaning in the presence of clinical signs related to a chronic inflammatory state are also reasonable motives to pursue AN. Series are mainly inconclusive but favor no overall benefit of AN on allograft survival after retransplant. This topic maintains interest in the transplant field and is particularly relevant for patients who are likely to require retransplantation within their lifetime. Further assessment is needed in the form of randomized controlled trials while controlling for various AN indications, immunosuppression regimens and with clearly defined survival outcomes.